A LOOK AND A LISTEN FOR THE DIFFERENCE - Chaves de Souza Pelogia, Eugênia (Health and Society, 2022)
The purpose of this text is to think about an inclusive education, through the praxis in psychopedagogy, where the education professional through the “space between” the subject who learns and the object of knowledge can direct a look and a singular listening, with the purpose of to act on the potentiality of the subject/learner and not on his/her difficulties, and in this way contribute for this subject to live their own experiences and place themselves as the author of their knowledge, so that the “possible inclusion” takes place. And, to enrich the idea, the text presents a clinical case where the expansion of the look, the listening and the reception of the psychopedagogue regarding the subject who learns, as well as his relationship with the world in which he is inserted, provided that the perception of those involved in the family/school context offered the necessary conditions to the learner, authorizing him/her to find his/her place as a subject, different from the other.